Safety and efficacy of ertugliflozin in Asian patients with type 2 diabetes mellitus inadequately controlled with metformin monotherapy: VERTIS Asia. Issue 6 (5th April 2019) - Ji, Linong; Liu, Yanmei; Miao, Heng; Xie, Yongli; Yang, Ming; Wang, Wei; Mu, Yuting; Yan, Ping; Pan, Sharon; Lauring, Brett; Liu, Shu; Huyck, Susan; et al.
Abstract : Aim: Phase III, randomized, double‐blind study evaluating the efficacy and safety of ertugliflozin in Asian patients with type 2 diabetes mellitus (T2DM) inadequately controlled on metformin, including evaluation in the China subpopulation. Materials and methods: A 26‐week, double‐blind study of 506 Asian patients (80.2% from mainland China), randomized 1:1:1 to placebo, ertugliflozin 5‐ or 15 mg, was performed. Primary endpoint was change from baseline in HbA1c at week 26. Secondary endpoints were change from baseline at week 26 in fasting plasma glucose (FPG), body weight (BW), systolic/diastolic blood pressure (SBP/DBP), and proportion of patients with HbA1c <7.0%. Hypotheses for the primary endpoint and FPG and BW secondary endpoints were tested in the China subpopulation. Results: At week 26, least squares mean (95% CI) change from baseline HbA1c was significantly greater with ertugliflozin 5‐ and 15 mg versus placebo: −1.0% (−1.1, −0.9), −0.9% (−1.0, −0.8), −0.2% (−0.3, −0.1), respectively. Ertugliflozin significantly reduced FPG, BW and SBP. Reductions in DBP with ertugliflozin were not significant. At week 26, 16.2%, 38.2% and 40.8% of patients had HbA1c <7.0% with placebo, ertugliflozin 5‐ and 15 mg, respectively. 59.3%, 56.5% and 53.3% of patients experienced adverse events with placebo, ertugliflozin 5‐ and 15 mg, respectively. Incidence of symptomatic hypoglycaemia was higher for ertugliflozin 15 mg vs placebo. Results in the China subpopulation were consistent. Conclusions: Ertugliflozin significantly improved glycaemic control and reduced BW and SBP in Asian patients with T2DM. Ertugliflozin was generally well‐tolerated. Results in the China subpopulation were consistent with the overall population.ClinicalTrials.gov : NCT02630706.